Interactive road sign awareness / Noor Diyana Atiqah Ab Latif - Ab Latif, Noor Diyana Atiqah (2011)
Multimedia offers lots of advantages in the field of education. An interactive multimedia application is one of the techniques in the multimedia fields. It has become a trend of the educational approach. It aims to make teaching and learning more interactive and engaging to achieve educational purposes. As a road user, it is really important to know and learn the road signs that have been built along the road. Users also need to be aware about the road signs in order to prevent them from anything bad happened while on the road. Therefore, in order to make the learning process become more interactive, a multimedia application has been implemented to help the users learn a bout the road signs. The methodology that has been chosen in developing this prototype is Spiral Methodology. A functional test conducted on the prototype showed that the prototype usable and function well.